Factors influencing the productivity and efficiency of wheat farmers in Punjab, Pakistan - Battese, George E.; Nazli, Hina; Smale, Melinda (Emerald Publishing Limited, 2017)
Scientists in Pakistan are currently developing biofortified wheat varieties to address widespread zinc deficiency, especially among women and children in poorer rural households. The purpose of this paper is to understand how the productivity and efficiency of small-scale and marginal wheat farmers can be improved so that their households may benefit from zinc-fortified varieties.The authors estimate a stochastic frontier production function model with data from a survey of wheat farmers conducted in Punjab, Pakistan in 2011.The productivities of the newer varieties of wheat were significantly greater than the older varieties, as expected. Farmers growing wheat in the rice-wheat and cotton-wheat zones tend to be more efficient than farmers from the mixed zone. Farmers who wait to adopt a leading variety are not less efficient than earlier adopters, but the longer the time until they switch varieties again, the more inefficient is their wheat production. Older farmers tend to be more technically inefficient than younger farmers, but the effect of education is not statistically significant. Wheat farmers with access to extension advice are more efficient. Farmers whose land suffered from severe salinity or severe toxicity are less productive and less efficient than others.The authors find no differences in technical inefficiency effects associated with growing the four most popular varieties, either grown alone or with other varieties – suggesting that no single leading variety should be targeted for biofortification. In contrast to some earlier studies, the authors find that small-scale farmers tend to be less technically efficient. This result underscores the need to specifically target this group in promotional programs, and also to complement these with reinforcement of agronomic recommendations.This project is part of the HarvestPlus program to determine the appropriate variety or varieties to biofortify with zinc so that Pakistan’s population can have better health and well-being. Further, the results show that there it is desirable to undertake further studies to improve the productivity and efficiency of wheat farmers in the Punjab, Pakistan to increase the health and well-being of the population in general.